Is onchocerciasis elimination in Africa feasible by 2025: a perspective based on lessons learnt from the African control programmes - Yankum Dadzie; Uche V. Amazigo; Boakye A. Boatin; Azodoga Sékétéli (BMC, 2018)
Abstract Background Onchocerciasis is found predominantly in Africa where large scale vector control started in 1974. Registration and donation of ivermectin by Merck & Co in 1987 enabled mass treatment with ivermectin in all endemic countries in Africa and the Americas. Although elimination of onchocerciasis with ivermectin was considered feasible only in the Americas, recently it has been shown possible in Africa too, necessitating fundamental changes in technical and operational approaches and procedures. Main body The American programme(OEPA) operating in onchocerciasis epidemiological settings similar to the mild end of the complex epidemiology of onchocerciasis in Africa, has succeeded in eliminating onchocerciasis from 4 of its 6 endemic countries. This was achieved through biannual mass treatment with ivermectin of 85% of the eligible population, and monitoring and evaluation using serological tests in children and entomological tests. The first African programme(OCP) had a head start of nearly two decades. It employed vector control and accumulated lots of knowledge on the dynamics of onchocerciasis elimination over a wide range of epidemiological settings in the vast expanse of its core area. OCP made extensive use of modelling and operationalised elimination indicators for entomological evaluation and epidemiological evaluation using skin snip procedures. The successor African programme(APOC) employed mainly ivermectin treatment. Initially its objective was to control onchocerciasis as a public health problem but that objective was later expanded to include the elimination of onchocerciasis where feasible. Building on the experience with onchocerciasis elimination of the OCP, APOC has leveraged OCP's vast modelling experience and has developed operational procedures and indicators for evaluating progress towards elimination and stopping ivermectin mass treatment of onchocerciasis in the complex African setting. Conclusions Following the closure of APOC in 2015, implementation of onchocerciasis elimination in Africa appears to overlook all the experience that has been accumulated by the African programmes. It is employing predominantly American processes that were developed in a dissimilar setting from the complex African onchocerciasis setting. This is impeding progress towards decisions to stop intervention in many areas that have reached the elimination point. This article summarizes lessons learned in Africa and their importance for achieving elimination in Africa by 2025.